Stacking subsidies in factor markets: Evidence from market experiments - Anthony Baffoe-Bonnie; Christopher Bastian; Dale J. Menkhaus; Owen R. Phillips (Journal of Risk and Financial Management, 2021)
Government policies employ different support programs such as subsidies to reduce risks, increase efficiency in markets, and enhance societal welfare. In markets such as ethanol markets, where multiple agents receive subsidy, it is often difficult to determine whether recipients of these support programs will transfer some of their payments to other agents in the market. In this study, we use laboratory market experiments to understand subsidy incidence in markets where both buyers and sellers receive subsidies, and there are few buyers relative to sellers. Our results show that when subsidizing both sides of the market, framing effects matter, and when markets are buyer concentrated, subsidy distributions generally tend to favor buyers. With a per-unit subsidy of 20 tokens to both sides and an equal number of buyers and sellers in the market, we find that buyers increase their earnings by 13.4% while seller earnings decrease by 16.1%. On a per-schedule basis, buyer earnings in the concentrated market are similar to what we observed in the competitive market.
Keywords: 330; subsidy incidence; laboratory experiments; energy markets; forward delivery markets